Environmental Extremes Are Associated with Dietary Patterns in Arabian Gulf Reef Fishes - Shraim, Rasha; Dieng, Mame M.; Vinu, Manikandan; Vaughan, Grace; McParland, Dain; Idaghdour, Youssef; Burt, John A. (Frontiers in Marine Science, 2017)
Climate change is affecting the trophic ecology of reef fishes through changes in reef-associated food availability and fish feeding behavior. The southern Arabian Gulf is a thermally extreme environment, providing an opportunity to study fish diets on reefs with summer temperatures representative of next-century conditions elsewhere. Using 18S metagenomic analyses of stomach contents, we provide the first description of the dietary composition of three abundant reef fishes (Pomacanthus maculosus, Pomacentrus aquilus, and Pomacentrus trichrourus) from the thermally extreme southern Arabian Gulf, with five sampling periods across 1 year used to assess seasonal variation in diet. In total, 146 stomach content samples were sequenced, resulting in 9.6 million filtered reads that aligned to 17 classes in 14 phyla. Corals (Cnidaria, Anthozoa) dominated stomach contents of all three fishes (overall mean: 74.6, 40.6, and 21.2% of stomach reads, respectively), suggesting coral consumption to be characteristic of reef fish diet in the region. Sanger sequencing validated the presence of corals in the stomach contents and identified two common genera in the region, Porites and Platygyra, as part of the diet. Other common phyla included sponges and annelid worms (P. maculosus: 14.9%, 4.1%; P. aquilus: 5.9%, 16.7%; P. trichrourus: 8.2%, 14.7%, respectively), with the remainder comprised of 11 other phyla. Algae were virtually absent in diets of all three species. The P. maculosus diet was consistently coral/sponge dominated across the year, but there was substantial seasonal variation in the damselfishes, with diets dominated by coral in the hottest month (August; P. aquilus: 89.4%, P. trichrourus: 51.5%) but broadest in spring (March, May) when corals became less common (<19.8% each) and bivalves, free living ascidians, and various arthropods increased; parasitic cestodes were also abundant in damselfish stomachs in spring (mean: >16.4%). These results suggest that these fishes have developed a feeding ecology responsive to the fluctuating and extreme environmental conditions of their region. These results broaden our understanding of the diets of these three species and document the nature, complexity and temporal dynamics of reef fish diets in the most thermally extreme coral reef environment on earth.